Fostering Positive Student-Teacher Relationships: A Literature Study On Positive Relationships and Their Impact on Academic and Social Outcomes - Ria, Gusriana Rahmayani; Eliasa, Eva Imania (Innovative: Journal Of Social Science Research, 2024)
Teacher-student relationships play an important role in improving academic outcomes, student engagement, and emotional well-being. However, building these positive relationships is still a challenge in education. The study identifies best practices, such as consistent support, effective communication, and student character development, as key steps in strengthening the teacher-student relationship. Through the Systematic Literacy Review approach, data analysis shows that open communication and inclusive teaching styles can increase learning motivation, academic achievement, and reduce student behavioral problems. This study emphasizes the importance of developing teacher education and training policies to improve quality interaction. In addition, a holistic and adaptive approach is needed to face challenges, especially in the era of online learning. This research is expected to be a reference for educators and policymakers in creating an inclusive education system that focuses on developing students' character. Keywords: Teacher-Student Relationship, Positive Relationship, Academic Outcomes